Youth perception of interaction and frequency of use in social networks - Gómez Rubio, Leire; López Vidales, Nereida (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Social networks are part of young people's personal growth and development. Their consultation and presence on them is no longer an option but a necessity. In this article we analyse the perception that young Spaniards have of the factors that motivate them to choose the profiles they follow on social networks and the trust they place in the content they publish. We surveyed 935 young people aged between 16 and 25, the results of which were supplemented by three focus groups. Among the results obtained, it is worth highlighting the lack of importance they attach to the recommendations of their contacts and the lack of intentionality in choosing profiles. Young people show a strong distrust of the content published on networks, including that of experts, because networks allow them to choose and give their opinion on any subject, regardless of their knowledge.